Review of Creativity and The Paris Review Interviews: A Discourse Analysis of Famous Writers’ Composing Practices by Rhonda Leathers Dively - Heidi M. Williams (Journal of the Assembly for Expanded Perspectives on Learning, 2022)
Only by fate and fortune would an apprentice receive the opportunity to review the work of a master. Nearly 14 years after sitting as a doctoral student in her Creativity Theory course, I am pleased to review Dr. Ronda Leathers Dively’s text, Creativity and The Paris Review Interviews: A Discourse Analysis of Famous Writers’ Composing Practices. Dively has written and published on the topic of Creativity Theory since the late 90s and is notably one of the pioneers for applying Creativity Theory in the composition and expository writing classrooms.
Keywords: JAEPL